Am I Sámi Enough? Narratives as a Means of Exploring a Sámi Pedagogy for Kindergarten - Kleemann, Carola Babette (Brill, 2024)
“Muitalus” is “story” or “narrative” in North Sámi. The word is closely related to the word for “remember” – “muitit”. The objective of narrative inquiry is to transform those who are participating. Such an enquiry must carry expectations for the future. In indigenous societies, telling stories has always been a means of transferring knowledge, sharing knowledge of expected behavior, or learning experiences. From the stories and the process of storytelling in a research project on language vitalization in a Sámi kindergarten department, I explore three themes in this article: language, identity, and Sámi pedagogy as experienced in Sámi practices. The stories are not merely material for this article, but they have been, and continue to be, a way of making ourselves – the participants – conscious about who has the power of defining Sámi, and how we, with our backgrounds may, or have the right to, work with strengthening Sámi language and culture in a Sea-Sámi area.